Functional Food Innovation Based on Fermented Milk Products with Fortification of Various Types of Tea: A Review: Inovasi Pangan Fungsional Berbasis Produk Susu Fermentasi dengan Fortifikasi Berbagai Jenis Teh: Review - Fadhlurrohman, Irfan; Susanto, Jodi (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2024)
Today's people tend to consume healthy food, for example, functional food. Functional foods from fermented milk products which contain many bioactive compounds include yogurt, kefir, and cheese. The nutritional value of this product can be further increased through fortification of various types of tea. This research aims to summarize results related to the fortification of various types of tea in yogurt, kefir, and cheese products as a functional food innovation based on fermented milk. Based on various research, tea fortification in fermented milk products can increase the functional value of the product. Fortification of green tea, oolong tea, white tea, and black tea as much as 0.5 – 4% has been proven to increase the total phenolic content, antioxidant activity, antimicrobial and LAB growth as well as produce better color, texture, and sensory properties of yogurt. Green tea and black tea fortification of 1 – 4% is also believed to produce kefir with better antimicrobial and antioxidant activity and has a lower calorific value than products without tea fortification. Cheese with green tea or orthodox black tea fortification of 0.1 – 2% or 2 g/kg has been proven to be able to enrich polyphenolic compounds up to 2 times, and the antiradical activity of the cheese is up to 44%, and the antioxidant activity of the cheese is 14% higher than the control. Based on the research that has been carried out, it is believed that the fortification of various types of tea in yogurt, kefir, and cheese products can be an innovation in the development of functional food which can have a better impact on body health.